Young adults' sought gratifications from, and perceptions of food advertising by, social media influencers: a qualitative approach - Ghada Talat Alhothali; Najlaa M. Aljefree (BMC, 2023)
Abstract Background This study aims to explore young adults' sought gratifications from social media influencers and whether they are exposed to food advertising by influencers. Further, it aims to understand how young individuals perceive food advertisements by social media influencers. Methods This qualitative study was conducted on 17 students from two public universities-King Abdul Aziz and Jeddah universities-located in the City of Jeddah, Saudi Arabia, using in-depth, face-to-face, and semi-structured interviews. The participants were active users of social media platforms who followed at least one influencer. Thematic analysis was used to analyse the data. The COREQ guidelines for reporting qualitative research (see Additional file 2) were followed when stating the findings. Results The findings reveal ten themes, that is, seven gratifications sought by young adults-broadening knowledge, perceived usefulness, self-improvement, boosting positivity, fostering morale, reinforcing inspiration, and passing time/enjoyment-and three themes (i.e. repeated, authentic, and unhealthy) that describe how Saudi young adults perceive food advertising. Conclusion This study contributes to social media influencer marketing by identifying the factors that motivate young consumers to follow influencers, and it elucidates the extent to which young adults are exposed to food marketing, adding to the body of literature on food advertising.